Identifying agricultural pesticides that may pose a risk for birds - Tassin de Montaigu, Cannelle; Goulson, Dave (PeerJ, 2020)
In this study, we analyze changing patterns of pesticide use in agriculture in Great Britain over the 1990–2016 period, with respect to the risk they pose to birds. The weight of pesticides applied decreased by 51% between 1990 and 2016, but the area treated increased by 63% over the same period. Over this period, there has been considerable turnover in the pesticides used. The European Union (including Great Britain until 2020) has restricted or banned many pesticides for agricultural use, including organophosphates and carbamates. However, new generations of active substances have been introduced, such as the neonicotinoids, some of which have since been banned. In this analysis, we estimate the annual ‘toxic load’ of agricultural pesticide use in Great Britain for birds, measured as the total number of LD50 doses for corn buntings, Emberiza calandra. We have previously performed similar analyses for bees, for which the total toxic load increased six-fold during this period. In contrast, for birds the total toxic load fell by 80.5%, although still correspond to 8.3e+11 corn bunting LD50 doses in 2016. The decrease in toxicity is largely due to declining use of highly toxic organophosphates in recent years. We identify the pesticides in current use that may pose the highest risk to birds, which include a mix of insecticides, herbicides, fungicides, molluscicides, acaricides and plant growth regulators. The insecticide ethoprop was ranked highest in 2016, with a toxic load of 71 billion potential corn bunting kills. Some of the other chemicals presenting a high toxic load, such as the herbicide chlormequat, are not highly toxic to birds (in terms of LD50) but are used in very large quantities. However, it is important to stress that, in reality, only a tiny proportion of pesticides applied will be ingested by birds, and this will vary according to timing and method of application, persistence of the active substance and many other factors. We further note that impacts of pesticides on birds might often be indirect, for example via depleting their food supply, and that sublethal impacts may occur at much lower doses than the LD50, neither of which do we investigate here. Nonetheless, we suggest that this is a useful approach to highlight pesticides that might be worth closer study with regard to possible impacts.
Keywords: Toxicity; LD50; Corn bunting; Emberiza calandra; Pesticides; Ethoprop; Chlormequat; Great Britain